HEAT TRANSFER CHARACTERISTICS OF NANOFLUID FLOW AROUND A ROTATING CYLINDER - YACINE, Khelili; ALLALI, Abderazzak; BOUAKKAZ, Rafik (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The forced convective flow and heat transfer of nanofluids past a rotating cylinder placed in a uniform cross stream is investigated numerically. The computations are carried out at a representative Reynolds number (Re) of 200. The dimensionless cylinder rotation rate (α) is varied between 0 and 6. The range of nanoparticle volume fractions (φ) considered is 0 ≤ φ ≤ 5%. Two-dimensional and unsteady mass continuity, momentum, and energy equations have been discretized using finite volume method. SIMPLE algorithm has been applied for solving the pressure linked equations. The effect of rotation rates (α) on fluid flow and heat transfer were investigated numerically. In addition, time-averaged (lift and drag coefficients and Nusselt number) results were obtained and compared with the literature data. A good agreement was obtained for both the local and averaged values.